Pharmacists' knowledge about use of topical corticosteroids in atopic dermatitis: Pre and post continuing professional development education. (5th April 2015) - Smith, Saxon D; Lee, Andrew; Blaszczynski, Alex; Fischer, Gayle
Abstract: Background/Objectives: Topical corticosteroids (TCS) are the standard of care in paediatric atopic dermatitis (pAD). Parents commonly cite TCS phobia as a major impediment to treatment adherence. Misinformation on TCS side‐effects can impact on perceptions of TCS safety. We aimed to assess pharmacists' beliefs and information on the safety of TCS in pAD treatment and determine whether their beliefs could be modified. Methods: Australian pharmacists attending a continuing professional development conference were assessed before and after an evidence‐based lecture on the use of TCS in pAD. Responses were recorded in real time on electronic keypads. Results: The mean response rate was 86% of the 292 surveyed. Of responders, 64% recognised that treatment non‐adherence was a major reason for treatment failure in pAD. The post‐education session assessment demonstrated a major attitude shift compared to the pre‐education assessment. After education, pharmacists would instruct parents/patients to apply TCS until the eczema is clear (27 vs 92% pre and post‐education, P  < 0.0001). The proportion that would instruct patients to use TCS sparingly dropped from 54 to 8% ( P  < 0.0001). The belief that cutaneous atrophy was the commonest side‐effect dropped from 46 to 7% ( P  < 0.0001). The belief that side‐effects from TCS would occur, even if used appropriately, dropped from 56 to 11% post‐education ( P  < 0.0001). Conclusions: The significant knowledge gaps about the use and safety of TCS in pAD in Australian pharmacists and their advice to patients potentially contributes to poor treatment concordance. These attitudes appear modifiable through targeted, evidence‐based education delivered by a dermatologist.